2000
DOI: 10.1007/s000590050023
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Myocarditis: Diagnosis and Treatment

Abstract: Giant cell myocarditis is a rare but devastating disease that usually affects young otherwise healthy individuals. Associations with thymoma, inflammatory bowel disease, and a variety of autoimmune disorders have been reported. The rate of death or heart transplantation is approximately 70% at 1 year. Data from a Lewis rat model and from observational human studies suggest that giant cell myocarditis is mediated by T lymphocytes and may respond to treatment aimed at attenuating T cell function. Recent findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
105
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 63 publications
0
105
1
6
Order By: Relevance
“…[17][18][19] However, electron microscopic studies to date have not identified viral particles in GCM, and no microbiologic agent has been directly identified in cardiac tissue by microscopy, tissue culture, or inoculation in experimental animals. 4,20 GROSS AND HISTOLOGIC FINDINGS Giant cell myocarditis is most commonly diagnosed via endomyocardial biopsy (52%), evaluation of the heart at autopsy (23%) or explantation (21%), or via examination of apical wedge sections removed at the time of ventricular assist device placement (4%). 5 On gross examination, cardiomegaly is frequently noted: in one series, the average heart weight in GCM was 476 g with a range of 405 to 580 g. 21 Serial sections typically reveal left or biventricular hypertrophy with accompanying dilatation.…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…[17][18][19] However, electron microscopic studies to date have not identified viral particles in GCM, and no microbiologic agent has been directly identified in cardiac tissue by microscopy, tissue culture, or inoculation in experimental animals. 4,20 GROSS AND HISTOLOGIC FINDINGS Giant cell myocarditis is most commonly diagnosed via endomyocardial biopsy (52%), evaluation of the heart at autopsy (23%) or explantation (21%), or via examination of apical wedge sections removed at the time of ventricular assist device placement (4%). 5 On gross examination, cardiomegaly is frequently noted: in one series, the average heart weight in GCM was 476 g with a range of 405 to 580 g. 21 Serial sections typically reveal left or biventricular hypertrophy with accompanying dilatation.…”
Section: Pathogenesismentioning
confidence: 99%
“…In the United States in the 1990s, a group of major heart failure referral centers reportedly diagnosed GCM (via autopsy, endomyocardial biopsy, apical wedge resection, or cardiac explantation) an average of once every 21 months. 4 Historically, GCM and cardiac sarcoidosis were often conflated, as both presented in similarly aged patients and could result in a myocarditis characterized by giant cells and granulomas. However, it has since been established that the two are distinct clinicopathologic entities with significant differences in presentation, histologic features, and prognosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In issue 6 of HERZ this year, we reexamined some of the most recent developments in experimental genetic models of heart failure, from zebrafish and mice by Kloos, Katus, and Meder [2] and patients with dilated cardiomyopathy by Ruppert and Maisch [3] and Wicks and Elliot [4], to the diagnosis and treatment of giant cell myocarditis by Cooper and ElAmm [5], viral myocarditis by Kühl et al [6], and autoreactive myocarditis by Maisch and Pankuweit [7], of right ventricular cardiomyopathy by Thiene et al [8], restrictive cardiomyopathy by Zwas et al [9], as well as the remodeling and adverse remodeling process after myocardial infarction by Brenner and Ertl [10]. Biomarkers of inflammation, particularly interleukin 10, were examined by Izumi and Nishii [11].…”
mentioning
confidence: 99%